The impact of brazilian samba on parkinson’s disease: Analysis by the disease subtypes O impacto do samba brasileiro na doença de parkinson: Análise através dos subtipos da doença El impacto del samba brasileño en la enfermedad de parkinson: Análisis a través de los subtipos de la enfermedad - Tillmann A.C.* (2020)
© 2020, Redprint Editora Ltda. All rights reserved.Introduction: People with Parkinson’s disease constantly have low levels of physical activity. Dancing has become increasingly important for treating the disease and can help improve non-motor symptoms. Objective: To analyze the influence of Brazilian samba on the non-motor symptoms of PD according to TD and PGID subtypes. Methods: A 12-week, non-randomized clinical trial, through comparison with a control group. The 23 individuals who agreed to participate in the activities formed the experimental group (EG) and the 24 individuals who opted not to participate in the Brazilian samba classes comprised the control group (CG). A questionnaire was applied, composed of validated instruments. Mini Mental State Examination – MMSE; HY – Disability Scale; Unified Parkinson’s Disease Rating Scale – UPDRS 1 and total values; Parkinson’s Disease Questionnaire – PDQ-39, Parkinson’s Disease Sleep Scale – PDSS; Beck Depression Inventory – BDI; Fatigue Severity Scale – FSS and Magnitude of Perceived Changes. Results: After the twelve weeks of intervention, it was observed that the EG showed improvement in the scores of all the tests. The comparison between groups, however, indicated a significant difference in the post-UPDRS1 period in which the EG presented improvement in cognitive impairment, while the CG presented a deficit in these values. The results of the division between disease subtypes show a greater change in the values between individuals of the TD group, when comparing the EG with the CG. For the EG, the greatest difference between pre- and post- intervention was fatigue. Conclusion: There was a positive trend in all the variables studied after the application of the protocol. This demonstrates that interventions such as dance may have greater effects on non-motor symptoms, depending on the expected progression of the disease. The scarcity of studies that use this approach in their analyses may explain the lack of evidence in this symptomatology related to dance. Level of evidence II; Therapeutic studies – Investigating the results of treatment.